Bridging the gap: advancing cancer cell culture to reveal key metabolic targets - Kes, Marjolein M. G.; Berkers, Celia R.; Drost, Jarno (Frontiers in Oncology, 2024)
Metabolic rewiring is a defining characteristic of cancer cells, driving their ability to proliferate. Leveraging these metabolic vulnerabilities for therapeutic purposes has a long and impactful history, with the advent of antimetabolites marking a significant breakthrough in cancer treatment. Despite this, only a few in vitro metabolic discoveries have been successfully translated into effective clinical therapies. This limited translatability is partially due to the use of simplistic in vitro models that do not accurately reflect the tumor microenvironment. This Review examines the effects of current cell culture practices on cancer cell metabolism and highlights recent advancements in establishing more physiologically relevant in vitro culture conditions and technologies, such as organoids. Applying these improvements may bridge the gap between in vitro and in vivo findings, facilitating the development of innovative metabolic therapies for cancer.